Thermoelectric Materials and Devices for Power Generation [Presentation] - Sabri, Mohd Faizul Mohd (My University, 2019)
Alternative renewable energy sources are becoming increasingly important due to the increase in worldwide energy needs and the adverse environmental effects of energy derived from fossil fuel burning. Thermoelectric generators (TEGs) have been identified as a viable technology for waste energy harvesting, from heat into electricity. In addition, thermoelectric (TE) technology is seen to be more environmentally compatible, due to its ability to convert heat directly into electricity without CO2 emission. The key to successful realization of this technology on a commercial scale lies largely with the performance of the thermoelectric material which drives this technology. However, the performance of this technology for commercial devices is still limited due to their low conversion efficiency of ~10–15%. In recent years, great progress has been made in improving their dimensionless figure of merit (ZT), which determines the conversion efficiency of TE devices. ZT is related to three “interlocked” factors—the Seebeck coefficient, electrical conductivity, and thermal conductivity. These three factors are interdependent in bulk TE materials, and the increase in one parameter has the possible effect of reducing the other two, thus resulting in a limit to the overall performance.
Keywords: Presentation; Thermoelectric materials; Devices for power generation; Malaya